Pendugaan Tingkat Produktivitas Pertanian Lahan Kering dengan Metode Indeks Storie di Kecamatan Raya Kabupaten Simalungun - Apong Sandrawati; Arion Eudia Saragih Garingging (Fakultas Pertanian Universitas Padjadjaran, 2016)
The aimed of this research was to find out the level of agricultural land productivity at Raya SimalungunSubdistrict with Storie Index Method. This research had been done since March–May 2014 at Raya Simalungun Subdistrict. Sampling spot was done at the certain agricultural landused, slope, and types of soil. Land use types consist of dry land agriculture and plantation. The slopes consisted of land with vary on declivity; 2-15%, 15-25%, 25-40% and >40%, meanwhile the soil’s types include Tropaquepts, Dystrandepts, Haplorthox, Tropudults, Hydrandepts. The result of agriculture land basedon several factors; dynamic factor of land such as drainage, erossion, pH, Electric Conductivity (EC) of soil layer, showed that the level of productivity of agricultural land in Raya Simalungun Subdistrict is Excellent Quality, Moderate, Poor and Very Poor. The most extensive land quality is at Grade 3 orMedium quality is amounted to 21,109.85 Ha or 88.65% of the area of dry land agriculture. Area of productive dry land agriculture in Raya Simalungun Subdistrict is 22,059.40 Ha or 92,63% and less productive land area is 1,754 Ha or 7.37 of area dry land agriculture. Key words: Productivity of agricultural land, storie index, texture, landuse, drainage, erossion, pH, Electric Conductivity (EC).